Covered or not covered: That is the question - Services classification and its implications for specific commitments under the GATS - Ruosi Zhang (World Trade Organization (WTO), 2015)
The GATS does not offer a definition of "services", but services need to be identified and classified for the operation of the Agreement, especially for the scheduling of specific commitments on market access and national treatment. There is no obligation on WTO Members to use any particular classification system in undertaking commitments. Nevertheless, an informal document produced for the services negotiation during the Uruguay Round, the Services Sectoral Classification List (W/120), was used and continues to be used as the principal guiding classification system, not only in the WTO, but also in bilateral and plurilateral services trade negotiations outside of the WTO. WTO jurisprudence has also noted the role of W/120 in the determination of sectoral coverage of GATS commitments. However, services classification does not receive enough attention it deserves. This paper attempts to make contribution by providing an overview of services classification and highlighting its relevance to both trade negotiations and WTO dispute settlement. It consists of four sections. Section I reviews how a services classification system was introduced into the multilateral trading system and describes the main features of W120. Section II takes a closer look at some aspects of the classification system, drawing attention to challenges in its application, which arise from inter alia services with multiple end-uses, overlaps between sectors, and the issue of "new services". Section III considers the implications of classification on GATS commitments by examining a number of WTO dispute settlement cases. Section IV concludes. In conclusion, the paper underlines the importance of services classification in assisting governments in clearly and accurately undertaking commitments. It also notes that WTO Members have taken or suggested various pragmatic approaches to addressing challenges in the application of the current services classification system. The proposed approaches again highlight the role of classification in ensuring the clarity, certainty and predictability of specific commitments in services.
Keywords: K33; 330; services classification; specific commitments; GATS